2018
DOI: 10.1007/s00520-018-4281-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-led medication assessment and deprescribing intervention for older adults with cancer and polypharmacy: a pilot study

Abstract: Purpose The aims of this study were to compare the application of three geriatric medication screening tools to the Beers Criteria alone for potentially inappropriate medication quantification and to determine feasibility of a pharmacist-led polypharmacy assessment in a geriatric oncology clinic. Methods Adult patients with cancer aged 65 and older underwent a Comprehensive Geriatric Assessment. A polypharmacy assessment was completed by a pharmacist and included a review of all drug therapies. Potentially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
149
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(164 citation statements)
references
References 22 publications
(23 reference statements)
4
149
1
5
Order By: Relevance
“…Moving forward, the study team will take ndings from this scoping review into a modi ed Delphi study to explore the signi cance of the identi ed TDF domains in Singapore's context, bearing in mind the potential for cultural and healthcare framework differences between Singapore and the studies included in this review. Building upon empiric evidence for pharmacist involvement in medication reviews, which has demonstrated improvements in prescribing practices and reduction in PIP [61][62][63][64] , our ultimate aim as a study team would be to develop a physician-pharmacist collaborative care intervention to guide effective prescribing for the older adults in the ambulatory setting.…”
Section: Resultsmentioning
confidence: 99%
“…Moving forward, the study team will take ndings from this scoping review into a modi ed Delphi study to explore the signi cance of the identi ed TDF domains in Singapore's context, bearing in mind the potential for cultural and healthcare framework differences between Singapore and the studies included in this review. Building upon empiric evidence for pharmacist involvement in medication reviews, which has demonstrated improvements in prescribing practices and reduction in PIP [61][62][63][64] , our ultimate aim as a study team would be to develop a physician-pharmacist collaborative care intervention to guide effective prescribing for the older adults in the ambulatory setting.…”
Section: Resultsmentioning
confidence: 99%
“…Moving forward, the study team will take findings from this scoping review into a modified Delphi study to explore the significance of the identified TDF domains in Singapore’s context, bearing in mind the potential for cultural and healthcare framework differences between Singapore and the studies included in this review. Building upon empiric evidence for pharmacist involvement in medication reviews, which has demonstrated improvements in prescribing practices and reduction in PIP [ 60 63 ], our ultimate aim as a study team would be to develop a physician-pharmacist collaborative care intervention to guide effective prescribing for the older adults in the ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…First, our results address an underinvestigated area that contributes to mortality in older allo-HCT patients. Second, the identification of potentially modifiable risk factors suggests that all older patients should benefit from pretransplant geriatric assessment and targeted interventions such as a pharmacist-led medication review, 46,47 pre-habilitation, and peritransplant delirium and fall prevention strategies. 32,37,43,48,49 We summarize potential prevention and intervention strategies in supplemental Table 4.…”
Section: Discussionmentioning
confidence: 99%